Corporate Social Responsibility Initiatives of Mcdonald's in Indonesia: Impact and Effectiveness - Angelina Wijaya Tan; Shirky Kharisma Fitri Hasnita; Hwihanus Hwihanus (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
This article examines the Corporate Social Responsibility (CSR) initiatives of McDonald's in Indonesia, focusing on their impact and effectiveness. Through the Ronald McDonald House Charities (RMHC), McDonald's has implemented various programs aimed at improving the health and well-being of underprivileged children and supporting local communities. The study highlights the positive effects of these initiatives on community welfare, corporate image, and consumer behavior. Additionally, it explores the strategic integration of CSR into McDonald's business model, emphasizing the importance of employee engagement and sustainable practices. The findings suggest that McDonald's CSR efforts have significantly contributed to social and environmental sustainability in Indonesia, setting a benchmark for other organizations. Future research should explore further enhancements to these initiatives to maximize their impact.